Harapan Orang Tua terhadap Peran Perawat pada Anak dengan Hospitalisasi (Studi Fenomenologi) - Yuliastati Yuliastati; Farial Nurhayati; Bram Burmana Jaya (Politeknik Kesehatan Tanjung Karang, 2019)
Hospitalization for children and parents is a very traumatic and stressful experience. Changes in the role, lack of sleep, feelings of pain, immobilization, unable to control yourself, a strange environment and changing daily habits are situations that are often felt by children that can trigger stress. For parents, stress occurs because of anxiety and fear resulting from the seriousness of the disease, procedures performed, treatment, the impact on the future of the child, frustration due to lack of information on procedures and treatment and unfamiliar hospital rules. Parental stress can be further increased when the health team shows an attitude of lack of empathy for them, limited information about caring for their children because of communication that is not well established with the health team, especially nurses and the involvement of parents in caring for their children. This study aims to identify what parents expect from the role of nurses when they care for their children in the hospital in this study. There are 5 themes: 1. Parental satisfaction over the improvement of the patient's condition, 2. Parental anxiety when the child is treated, 3. Adequate support for child care facilities 4. Communication barriers between patient-family nurses and 5. More attention is needed for pediatric patients from a nurse. This study is expected to improve the role of nurses, especially child nurses in carrying out nursing care according to the needs of patients and families.